Vortioxetine’s impact on the autonomic nervous system in depressed children and adolescents: analysis of the heart rate variability - Krivosova, Michaela; Hutka, Peter; Ondrejka, Igor; Visnovcova, Zuzana; Funakova, Dana; Hrtanek, Igor; Ferencova, Nikola; Mlyncekova, Zuzana; Kovacova, Veronika; Macejova, Andrea; Kukucka, Tomas; Mokry, Juraj; et al. (Scientific reports, 2024)
Relationship between depressive disorder and autonomic nervous system has been already discussed. Reduced emotional regulation is supposed to be associated with prefrontal hypofunction and subcortical hyperactivity. The aim of this study was to determine the effect of vortioxetine on heart rate variability (HRV), a parameter of cardiac autonomic regulation, in depressed hospitalized paediatric patients and assess the clinical effectiveness of the drug in this population. We performed repeated polysomnography analyses at admission and after a short treatment in hospital (15.2 days on average) and measured various HRV parameters (RRi, pNN50, RMSSD, LF-HRV, HF-HRV) during wakefulness, N3 and REM sleep stages. Out of 27 study subjects, 67% have improved depression symptoms as well as anxiety and subjective sleep quality after short vortioxetine treatment. We have found a significant decrease in parasympathetic parameters pNN50, RMSSD and HF-HRV during N3 sleep phase, though not exclusively among vortioxetine responders. The anticipated increase in cardiovagal regulation after vortioxetine treatment was not demonstrated in this pilot study, possibly due to the drug’s multimodal mechanism and impact on the nucleus tractus solitarii, particularly its antagonism on 5HT-3 receptors. Application of selective drugs could further explain the effect of vortioxetine on HRV in depressed patients.